1977
DOI: 10.1111/j.1471-0528.1977.tb12506.x
|View full text |Cite
|
Sign up to set email alerts
|

INTRAVENOUS OXYTOCIN AND ORAL PROSTAGLANDIN E2 FOR RIPENING OF THE UNFAVOURABLE CERVIX

Abstract: Summary A clinical trial involving 60 patients was conducted to assess the relative efficacy of intravenous oxytocin and oral prostaglandin E2 in ripening the unfavourable cervix, when given as a priming dose on the day before induction of labour. There was significant improvement in the Bishop score, and the subsequent induction‐delivery interval following priming with prostaglandin. This improvement appeared to be dose‐related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1980
1980
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…In a study by Golbus & Creasy (1977) the Bishop score was found to increase when PGE2 was used for priming the cervix before induction (7). Similar observations were made by Valentine (1977) and also by Pearce (1977) in a double-blind study (11, 10). However, Friedman & Sachtleben (1975) could not find any priming effect when using PGE2 tablets in their double-blind study (6).…”
supporting
confidence: 86%
“…In a study by Golbus & Creasy (1977) the Bishop score was found to increase when PGE2 was used for priming the cervix before induction (7). Similar observations were made by Valentine (1977) and also by Pearce (1977) in a double-blind study (11, 10). However, Friedman & Sachtleben (1975) could not find any priming effect when using PGE2 tablets in their double-blind study (6).…”
supporting
confidence: 86%
“…(Hannah 1996; Jagani 1984; McCaul 1997; Puertas 1996; Ray 1992; Roberts 1986; Van Der Walt 1989; Wiqvist 1986). Twenty-five trials compared oxytocin with a policy of expectant management (Akyol 1999; Alcalay 1996; Chang 1997; Damania 1992; Duff 1984; Grant 1992; Hannah 1996; Hjertberg 1996; Jagani 1984; Ladfors 1996; McCaul 1997; McQueen 1992; Morales 1986; Natale 1994; Ottervanger 1996; Puertas 1996; Ray 1992; Roberts 1986; Rydhstrom 1991; Sperling 1993; Tamsen 1990; Valentine 1977; Van Der Walt 1989; Wagner 1989; Wiqvist 1986). Twenty-seven trials compared oxytocin with vaginal PGE2 (Andersen 1990; Atad 1996; Chua 1991; Egarter 1987; Ekman 1986; Ekman-Ordeberg 1985; Griffith-Jones 1990; Hannah 1996; Herabutya 1991; Jagani 1984; Lange 1984; Legarth 1987; Lyndrup 1989; Lyndrup 1990; Macer 1984; Magos 1983; McCaul 1997; McQueen 1990; Olmo 2001; Pollnow 1996; Ray 1992; Roberts 1986; Rymer 1992; Silva-Cruz 1988; Valadan 2005; Van Der Walt 1989; Wilson 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Its exogenous use causes enough uterine activity to produce cervical dilation and fetal descent without uterine hyperstimulation or fetal distress (2). However, oxytocin is a poor cervical ripener (12, 102–105). It is usually not effective to use this hormone for labor induction without the presence of a ripe cervix.…”
Section: Methods Of Cervical Ripening and Labor Inductionmentioning
confidence: 99%